Pterocarpus erinaceus leaf extracts phytochemical composition and its effect on growth performance and intestinal microbial population of weaned rabbits - Alagbe, John Olujimi (Zien Journals, 2024)
In Sumitra Research Institute, a total of 50 crossbred male rabbits with initial body weight of 486 ± 0.70 g and weaned at 28 days of age were individually housed in a specially constructed galvanized cage was used to examine the effect of Pterocarpus erinaceus leaf extracts (PELE) on the growth performance and intestinal microbial population of weaned rabbits. Rabbits were stratified based on their body weight and assigned to 5 groups with six animals with one animal per replicate in a completely randomized design. Experimental diet was adequate in all nutrients to meet the requirement of rabbits. Animals in group 1 was fed standard diet with 0 mL PELE while group 2, 3, 4 and 5 were fed standard diet with 0.2 mL, 0.4 mL, 0.6 mL and 0.8 mL/day respectively.
Keywords: Pterocarpus erinaceus; phytochemicals; animal; rabbits